Precision medicine : tools and quantitative approaches - Deigner, Hans-Peter; Kohl, Matthias (Elsevier/Academic Press, 2018)
"Precision Medicine: Tools and Quantitative Approaches discusses precision and personalized medicine, two relevant topics that are revolutionizing diagnostics and treatment, while also providing a shift toward prevention. The book covers the most relevant features and explanations underlying developments in the field. A timely review on prerequisites, causes and consequences is given. Unique to this book is a combined view on technical and data analysis aspects that is mandatory for obtaining and interpreting results. This book is a valuable source for researchers in medical and life sciences, physicians and students with an interest in this emerging field of precision medicine"--Publisher's description